1997
DOI: 10.1017/s0790966700002858
|View full text |Cite
|
Sign up to set email alerts
|

Trainee attitudes towards their training and its supervision

Abstract: Objectives: To assess the experience and attitudes of trainees towards a range of aspects of their training in Psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Meagher et al 3 reported that 27% of trainees had experienced violence at work. A follow-up study showed that 16% of trainees had experienced violence at work, but more than two-thirds had no training in 'breakaway' techniques, only 25% were aware of a critical incident debriefing service in their area and most were dissatisfied with the induction training provided by their employers.…”
Section: Irish Studiesmentioning
confidence: 99%
“…Meagher et al 3 reported that 27% of trainees had experienced violence at work. A follow-up study showed that 16% of trainees had experienced violence at work, but more than two-thirds had no training in 'breakaway' techniques, only 25% were aware of a critical incident debriefing service in their area and most were dissatisfied with the induction training provided by their employers.…”
Section: Irish Studiesmentioning
confidence: 99%